Novel Aporphine- and Proaporphine-Clerodane Hybrids Identified from the Barks of Taiwanese Polyalthia longifolia (Sonn.) Thwaites var. pendula with Strong Anti-DENV2 Activity - I-Wen Lo; Geng-You Liao; Jin-Ching Lee; Chi-I Chang; Yang-Chang Wu; Yen-Yu Chen; Shang-Pin Liu; Huey-Jen Su; Chih-I Liu; Chia-Yi Kuo; Zheng-Yu Lin; Tsung-Lin Li; et al. (MDPI AG, 2022)
Hybrid natural products produced via mixed biosynthetic pathways are unique and often surprise one with unexpected medicinal properties in addition to their fascinating structural complexity/diversity. In view of chemical structures, hybridization is a way of diversifying natural products usually through dimerization of two similar or dissimilar subcomponents through a C-C or N-C covalent linkage. Here, we report four structurally attractive diterpene-alkaloid conjugates polyalongarins A-D (1-4), clerodane-containing aporphine and proaporphine alkaloids, the first of its kind from the barks of Taiwanese Polyalthia longifolia (Sonn.) Thwaites var. pendula. In addition to conventional spectroscopic analysis, single crystal X-ray crystallography was employed to determine the chemical structures and stereo-configurations of 1. Compounds 1-4 were subsequently subjected to in vitro antiviral examination against DENV2 by evaluating the expression level of the NS2B protein in DENV2-infected Huh-7 cells. These compounds display encouraging anti-DENV2 activity with superb EC50 (2.8-6.4 μM) and CC50 values (50.4-200 μM). The inhibitory mechanism of 1-4 on NS2B was further explored drawing on in-silico molecular docking analysis. Based on calculated binding affinities and predicted interactions between the functional groups of 1-4 and the allosteric-site residues of the DENV2 NS2B-NS3 protease, our analysis concludes that the clerodane-aporphine/proaporphine-type hybrids are novel and effective DENV NS2B-NS3 protease inhibitors.